MOTHeRS' Project Recipes - Craven, Kay; Smith, Brittany; Kolasa, Kathryn M (My University, 2020)
The MOTHeRS’ Project was developed in 2020 with funding from the United Healthcare Foundation (UHF), ECU Physicians, and the Departments of OB-GYN, Psychiatry and Family Medicine, to utilize NC-STeP—a statewide telepsychiatry program to bring multidisciplinary care to three community-based primary care obstetric clinics in Carteret, Duplin, and Chowan counties. Through this collaborative care model that includes the patient, nurse navigator, diabetes educator, behavioral health manager, primary obstetrician, MFM specialist, and a psychiatrist consultant, the MOTHeRS’ Project brings support and insights of specialty physicians to the identified practices. An additional component of this program will be the Medical Food Pantry to include healthy food bags and tailored patient education to women with high risk pregnancies and food insecurity, living in rural areas. This entry includes English and Spanish versions of The MOTHeRS' Project Recipe handout, available in both color and black-and-white. This 2-sided handout was designed to provide instruction and inspiration on how to use common food items that are good sources of nutrients identified to be important during pregnancy, but which are often under-consumed. Both sides of the handout include a brief description of each food item, its nutritional significance during pregnancy, and tips on how to use/cook with it. Additionally, detailed recipes are provided for some food items, and QR codes are available for others. Shelf-stable food items and foods provided in the MOTHeRS' Emergency Food Bag, or available with WIC-benefits are emphasized. The bottom of the back-side of the handout offers suggestions of nutritious snack combinations that can be enjoyed during pregnancy.
The authors are pleased to share these materials with others at no expense, please credit The MOTHeRS’ Project, Brody School of Medicine at East Carolina University. We would appreciate you telling us if/how you used these materials.
Keywords: MOTHeRS' Project Recipes; Pregnancy; Food Insecurity; Nutritious foods and snacks during pregnancy